2019
DOI: 10.1111/jfbc.12897
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of acetylcholinesterase inhibition by hemp seed protein‐derived peptides

Abstract: The aim of this work was to enhance the acetylcholinesterase (AChE)‐inhibitory activity of a pepsin‐produced hemp seed protein hydrolysates (HPH) through reverse‐phase HPLC separation followed by identification of peptide sequences present in the most active fraction. The HPH was separated into eight fractions (F1–F8) with F7 exhibiting significantly (p < 0.05) the strongest (97.5%) in vitro inhibition of electric eel AChE (eeAChE) activity in comparison to 53.8% for HPH. The HPH consisted mostly of low molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…Interestingly, PH and TH had the lowest number and longest length of identifiable peptides, which reflects the lower DH when compared to AH and CH. A previous study suggested that low molecular weight peptides have greater chance to pass through the gastrointestinal tracts faster than the peptides with bigger molecular weights, which could enhance bioactive effects [ 34 ]. Based on this principle, the small peptides identified in CH may have stronger bioactive impacts if ingested when compared to the other hydrolysates in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, PH and TH had the lowest number and longest length of identifiable peptides, which reflects the lower DH when compared to AH and CH. A previous study suggested that low molecular weight peptides have greater chance to pass through the gastrointestinal tracts faster than the peptides with bigger molecular weights, which could enhance bioactive effects [ 34 ]. Based on this principle, the small peptides identified in CH may have stronger bioactive impacts if ingested when compared to the other hydrolysates in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The method described by Malomo and Aluko [ 34 ] was used to identify the peptide sequences of the protein hydrolysates. Formic acid (0.1% v / v ) was used to dilute the sample to a final concentration of 10 ng/µL.…”
Section: Methodsmentioning
confidence: 99%
“…The presence of shorter peptides such as the dipeptides may suggest greater advantages to interact with and neutralize free radicals more effectively to inhibit propagation. In addition, all the identified peptides have molecular weights <500 Da and this may enhance the ease of absorption of the peptides from the gastrointestinal tract and improve in vivo activities [Malomo & Aluko, 2019]. Alcalase and chymotrypsin hydrolysates shared three (PGV, GVP, and RP) common peptides (2 tripeptides and 1 dipeptide) while pepsin and trypsin hydrolysates showed two (STGT and FKA) similar peptides.…”
Section: Peptide Sequencingmentioning
confidence: 99%
“…In addition, the hydrolysates of plant protein have unique physiological functions (22,(25)(26)(27)(28)(29). After digestion with different proteases, the hydrolysates of HSP were demonstrated to exhibit various physiological activities in vitro as well as in vivo, with hemp proteins short-chain peptides such as WVYY and PSLPA exhibiting antioxidant ability, GVLY and LGV exhibiting anti-hypertension ability, and the hydrolysates exhibiting antiproliferative and hypocholesterolemic activities (30)(31)(32)(33)(34)(35)(36).…”
Section: Introductionmentioning
confidence: 99%